DC MOTOR CONTROL USING GENETIC ALGORITHM BASED PID - SHAHRONI, NURUL ASHIKIN (Universiti Teknologi Petronas, 2011)
This dissertation presents the research that had been done on the chosen topic, works done and results acquired throughout the Final Year Project for two semesters, about the DC Motor Control using Genetic Algorithm based PID. The objectives of this project are to optimize speed control of the DC motor by using Genetic Algorithm based PID, to improve the performances of the DC motor controller in term of rise time, settling time, maximum overshoot and Integral of Time Absolute Error (ITAE) and to decide the best parameters to be used for Genetic Algorithm that can optimize the performance of a DC Motor ( eg: population size, mutation rate and crossover value). First, the report discusses the types of DC motor available in industry nowadays and the origination of Genetic Algorithm itself. Next, the paper sees the implementation of DC motor control and the tuning available that has been researched before. The usage of Genetic Algorithm is briefly explained which comprises of three main phases; reproduction, crossover and mutation. For this study, the software used is MATLAB/Simulink, where the implementation of the chosen DC motor model is represented and Genetic Algorithm is incorporated into the PID controller of the motor, to observe the performance of chosen parameters available. Next, the paper shows the results of PID controller tuning and also the results for the implementation of GA based PID controller. Comparison then is made and discussed to see whether the results are as expected. Lastly, recommendation and conclusion pertaining to the completion of this project are presented.